Insight. Pre-Intermediate: teacher's book - Krantz C. Caroline (Oxford Exam Support)
Teaching notes for every lesson in the Student's Book Ideas for additional activities Ideas for ways to support weaker students and stretch stronger students Culture and language notes. All the course DVD on the Teacher's Resource Disk with accompanying worksheets Photocopiable materials for communicative group and pair work activities.